Novel deadbeat predictive control strategy for DFIG’s back to back power converter - Manale Bouderbala; Badre Bossoufi; Hala Alami Aroussi; Mohammed Taoussi; Ahmed Lagrioui (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
To successfully carry out a wind energy conversion system, it is necessary to simultaneously control the rotor and the grid side. This paper proposes a doubly-fed induction generator's predictive power control. While the powers are controlled indirectly through currents, the latter is controlled using the deadbeat command. Based on discrete-time, the control suggests at each sample period the required voltages to the the-back-to-back converter to reach the desired setpoints, control the powers, and the DC link voltages. For these reasons, a presentation of the system is given first, then a description of the predictive control, followed by applying this strategy on the rotor side control and grid side control. Finally, a random wind profile was applied to analyze the system's performance with a unitary power factor. The simulation results are presented in the MATLAB/Simulink environment using a 1.5 kW DFIG. The results obtained by applying a random wind profile have well fulfilled the objectives of the control and the system robustness is approved by the excellent tracking allowing the machine's internal parameters variation. By comparing the quality and the tracking reference of the proposed control method to other control methods, the deadbeat controller was very promising.